2011
DOI: 10.5177/ntvt.2011.09.10267
|View full text |Cite
|
Sign up to set email alerts
|

Synoviale chondromatose van het temporomandibulaire gewricht. Een systematisch literatuuronderzoek naar de kenmerken

Abstract: Wat is nieuw?Een klinisch kenmerk van synoviale chondromatose van het temporomandibulaire gewricht dat niet typerend is voor temporomandibulaire disfunctie, is een vaste, stugge, niet fluctuerende zwelling om de laterale pool van het gewricht. PraktijktoepassingSynoviale chondromatose dient te worden overwogen bij de differentiële diagnostiek van patiënten met temporomandibulaire disfunctieklachten. Palpatie en röngtendiagnostiek kunnen de afwijking opsporen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Limited scientific evidence was also available to support the association between orthodontic treatment and TMD. A review carried out in 2007 by Mohlin et al confirmed these findings [ 46 ]. It discovered no link between certain malocclusions or orthodontic procedures and the symptoms of TMD.…”
Section: Reviewmentioning
confidence: 80%
“…Limited scientific evidence was also available to support the association between orthodontic treatment and TMD. A review carried out in 2007 by Mohlin et al confirmed these findings [ 46 ]. It discovered no link between certain malocclusions or orthodontic procedures and the symptoms of TMD.…”
Section: Reviewmentioning
confidence: 80%